2020
DOI: 10.1021/acs.chemmater.0c02258
|View full text |Cite
|
Sign up to set email alerts
|

High Mobility Preservation of Near Amorphous Conjugated Polymers in the Stretched States Enabled by Biaxially-Extended Conjugated Side-Chain Design

Abstract: Polymers with an abundant amorphous domain should facilitate energy dissipation upon stretching, making near amorphous π-conjugated polymers have immense potential in realizing intrinsically stretchable field-effect transistor (FET) devices. In this study, high mobility preservation under the stretched state is attempted by replacing typical alkyl-monothienyl (T-R) on a benzo­[1,2-b:4,5-b’]­dithiophene-difluorobenzothiadiazole backbone with three other biaxially extended side-chains, including alkyl-dithienyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 54 publications
2
61
0
Order By: Relevance
“…[ 24 ] Despite their amorphous nature, benzodithiophene‐based polymers with a biaxially‐extended side chain design also reveal high flexibility and a good charge carrier transport during deformation. [ 25 ] It was shown that polymers with abundant amorphous domains facilitate energy dissipation during stretching maintaining the charge carrier transport. The interdigitating and/or entanglement of these biaxially extended side chains are responsible for the mechanical robustness upon elongation.…”
Section: Introductionmentioning
confidence: 99%
“…[ 24 ] Despite their amorphous nature, benzodithiophene‐based polymers with a biaxially‐extended side chain design also reveal high flexibility and a good charge carrier transport during deformation. [ 25 ] It was shown that polymers with abundant amorphous domains facilitate energy dissipation during stretching maintaining the charge carrier transport. The interdigitating and/or entanglement of these biaxially extended side chains are responsible for the mechanical robustness upon elongation.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a possible explanation is an inhibition of the interdigitation effect detected at longer annealing times due to chain confinement in thin solid films. Indeed, several authors have explained how the interdigitation effect occurs in alkyl chains of conjugated polymers [20,21,26,35,36], reducing the volume of the crystalline arranges and presenting differences in FWHM between regioregular and regiorandom polymers. One of the studies [26] even points out that the methyl chain end on P3HT exhibits the closest packing, as in n-alkane crystallization, and causes a structural mismatch due to the difference between their packing density and the areal density of the attached ends.…”
Section: Resultsmentioning
confidence: 99%
“…To study the mobilitystretchability property of the PNDI2T film, a film transfer technique was applied according to the method reported in the literatures. 26,27 Briefly, a transferred/stretched film was prepared in a nitrogen-filled glove box by transferring the PNDI2T film onto an elastomeric poly(dimethylsiloxane) (PDMS) slab, and then the PNDI2T film supported by the PDMS slab was stretched and transferred back to the wafer substrate. Note that the film transfer process was conducted at 70 1C.…”
Section: Fabrication Of Fet Devicesmentioning
confidence: 99%
“…20 To improve the mobility-stretchability properties of n-type CPs without sacrificing their thermal and mechanical integrity, structural engineering should be used to maintain strength while improving the fracture strain of CPs. 21 The feasible approaches to structural engineering can be divided into three categories: (1) random copolymerization with dimensionally similar monomers, 22,23 (2) adoption of rigid fused-ring backbones for a near-amorphous structure, 24,25 and (3) introduction of conjugated side groups on the side chains to promote chain aggregation 26,27 or the combination of a fused-ring backbone and conjugated side groups. 28 Most of the methods capable of improving mobility-stretchability properties are applicable mainly to p-type CPs and are seldom reported in n-type CPs owing to the instability of carrier transport and limited types of backbones.…”
Section: Introductionmentioning
confidence: 99%